Effects of Soil Ameliorants Produced from Recycled Glass on the Establishment of Table Grapes - Myburgh, P.A.; Howell, C.L. (South African Journal of Enology and Viticulture, 2023)
Sandy, gravelly or stony soils with low nutrient supply or plant available water are common in the table grape growing regions of South Africa. A field study was carried out to determine if an ameliorant recycled from waste glass could enhance the nutrient and water supply during the establishing phase of table grapes. Two grades of ameliorant, i.e. fine and coarse, were incorporated into the soil before the grapevines were planted. No ameliorants were applied to the control. After planting, the grapevines were irrigated by using 2.1 L/h drippers. To establish whether the ameliorants could compensate if less water is applied, the same treatments were applied under 1.2 L/h drippers. In general, the grapevines responded positively to the higher irrigation volumes, irrespective of ameliorant application. Where higher irrigation volumes were applied, the ameliorants did not have any positive effect on soil chemical or grapevine nutrient status compared to the control. This showed that the ameliorants were chemically inert under the given conditions. The ameliorants also did not improve grapevine water status, vegetative growth, yield or juice characteristics. Likewise, the ameliorants could not compensate for any measured aspect of grapevine performance where less irrigation was applied. In general, the ameliorants did not meet the expectations. Considering the additional costs of the ameliorant application, and the lack of positive grapevine responses, this practice cannot be justified under the given, or comparable conditions.